(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2022)
The article is devoted to an extensive study of theoretical information about such stylistic phenomenon as charientismos. The place of this phenomenon is revealed in typology of language stylistic resources. The research is described the main ways for clarification of the concept “charientismos” and is offered author’s definition of it. The features of charientismos using in modern speech are also illustrated. We represent some moments of several-hundred-years-old history of tropes and figures of speech studies. Those moments that are become a strong foundation for developing of rhetorical and stylistic theory, but that are left plenty of unresolved and sometimes even controversial issues. The paper is focused on some stylistic phenomena that were deprived of attention, were really seldom examined at researches and only sometimes were appeared in linguistic circulation on so-called classical arrangement. One of them is charientismos. It has got the powerful stylistic potential that expresses hidden delicate-ridicule-critical speaker’s attitude to participants of communication. The attention is also drawn to the fact that charientismos is still “looking for” its place at the system of stylistic resources. It is belonged whether to tropes, or to stylistic figures of speech, or to quasi-tropes. At the same time offered modern classification schemes and defining this stylistic-rhetorical phenomenon are realized “according to tradition”. Delicate ridicule or mocking joke that is based on feigned prettiness, courtesy, in other word — charientismos, is considered from the position of realization both in verbal and in syntactic form. This way of investigation proves paradigmatic nature of creation that can obtain syntagmatic nature.